2003
DOI: 10.1002/ajpa.10260
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication:Age and fractal dimensions of human sagittal and coronal sutures

Abstract: The fractal dimensions of human sagittal and coronal sutures were calculated on 31 complete skulls from the Terry Collection. The aim was to investigate whether the fractal dimension, relying on the whole sutural length, might yield a better description of age-related changes in sutural morphology, as opposed to other methods of quantification, which generally rely on more arbitrary scoring systems. However, the fractal dimension did not yield better age correlations than other previously described methods. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…Previous anthropologic studies have suggested a slight increase in suture width among the adult male population versus the adult female population 16 ; however, an equivalent number of studies did not reach the same conclusion. 17 Results also were not stratified by ethnicity because previous studies have not found this effect to be statistically significant.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous anthropologic studies have suggested a slight increase in suture width among the adult male population versus the adult female population 16 ; however, an equivalent number of studies did not reach the same conclusion. 17 Results also were not stratified by ethnicity because previous studies have not found this effect to be statistically significant.…”
Section: Discussionmentioning
confidence: 72%
“…17 Results also were not stratified by ethnicity because previous studies have not found this effect to be statistically significant. 16,[18][19][20] Finally, the authors recognize the inherent limitation of assessing sutures that may be smaller than the section thickness of the acquired images. Reviewing both the transverse images and the cross-referenced scout images mitigated the section thickness limitation by allowing the authors to confirm that the location of measurement was representative.…”
Section: Discussionmentioning
confidence: 99%
“…This method experiences problems with both accuracy and precision of the determined age at death. By observing ectocranial sutures during autopsy activities, the authors focus their attention on the morphology of the sutures and their level of obliteration [1][2][3][4][5][6][7][8]. From a sample of 100 individuals, the inaccuracy and imprecision of the Meindl and Lovejoy method was evident.…”
Section: Introductionmentioning
confidence: 99%
“…This is equally true for linear measurements, such as the index of interdigitation (measured in cross-section by Rafferty and Herring, 1999) or sinuosity (measured in ectocranial view by Jaslow, 1990), as well as for fractal analysis of suture shape (Lynnerup and Jacobsen, 2003). For example, the index of interdigitation (Rafferty and Herring, 1999) can be identical for two sutures even though the sutures vary in interdigitation size (e.g., one suture may be composed of several small interdigitations in cross section, while the second exhibits a single large interdigitation).…”
mentioning
confidence: 99%
“…First, only one aspect of suture shape is described and measured. That is, the focus has only been on either the ectocranial expression of a suture (i.e., its linear trace on the surface of the skull) (see Jaslow, 1990;Hartwig, 1991;Anton et al, 1992;Monteiro and Lessa, 2000;Lynnerup and Jacobsen, 2003;Nicolay and Vaders, 2006), here termed ''sinuosity'', or on its cross sectional shape (i.e., an ecto-to-endocranial slice through the suture) (see Rafferty and Herring, 1999), here referred to as ''interdigitation.'' To describe and quantify the morphology of a suture more completely, the cross-sectional shape of a suture as well as its surface trace must be zconsidered.…”
mentioning
confidence: 99%